The Brain Management of Time and it's Correlative to the Creative Leadership of the Heads of Scientific Departments in the Faculties of Physical Education and Sports Sciences in Iraq - Jassem Jaber Mohammed (Journal of Global Pharma Technology, 2018)
The current research problem was identified by answering the following question:Is there a relationship between the effectiveness of time management, and the level of creative leadership of the heads of departments, in the faculties of physical education and sports sciences from the perspective of the members of the faculty and the objectives of the research was to identify the effectiveness of time management and creative leadership of the heads of departments in the faculties of physical education and sports sciences and identify the Iraqi The relationship between the degree of effectiveness of time management and creative leadership of heads of departments in the faculties of physical education and sports sciences in Iraq. The researchers used the descriptive approach in the two methods of surveying and interrelationships. The research community was determined by the professors of faculties of physical education and sports sciences in Iraq. The sample was randomly selected from the (Universities of Muthanna, Babel, Kufa, Karbala, Dhiqar, Missan, Kut, and Qadisiyah) as indicated in the table below. Characterization of research measures Since the current research aims to define the management of time and its relationship to the level of creative leadership of the heads of the scientific departments in the faculties of physical education and sports sciences of Iraq, it was necessary to achieve the objectives of the research tool to develop time management, by defining time management areas from the perspective of members of the Commission Teaching, and preparing a tool for the level of creative leadership by defining its areas from the point of view of faculty members as well. Defining the concept of the study variables: time management and creative leadership. Defining areas of time management and creative leadership as follows: The brain management of time: Planning - Organization - Human Relations - Decision Making - Follow-up and Evaluation. Creative Leadership Scale. The most important conclusions: The philosophy of department heads and their approach to time management and creative production as important elements in the management process is weak. There is a correlation between time management and positive creative leadership through the answers of faculty members. The main reasons that limit the professional level of the departments of the academic departments where the recommendations are the limited training courses in the field of management. And the need to prepare a guide to knowledge and guidance in the field of time management, and the creative capabilities of employees in the university institution. The availability of spatial and physical facilities to help prepare for the change process to ensure the sustainability and continuity of the work of faculties of physical education and sports sciences.Keywords: Brain management, Time, Creative, and leadership.